2018
DOI: 10.1021/acsphotonics.7b01390
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Organic Photovoltaics: Unraveling Plasmonic Enhancement for Realistic Cell Geometries

Abstract: Incorporating plasmonic nanoparticles in organic photovoltaic (OPV) devices can increase the optical thickness of the organic absorber layer while keeping its physical thickness small. However, trade-offs between various structure parameters have caused contradictions regarding the effectiveness of plasmonics in the literature, that have somewhat stunted the progressing of a unified theoretical understanding for practical applications. We examine the o p t i c a l e n h a n c e m e n t m e c h a n i s m s o f … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 98 publications
0
21
0
Order By: Relevance
“…Plasmonic NPs are widely studied for their strong scattering, absorption of light and fluorescence emission, enabling their application in several fields such as labeling, imaging, and electronics. In particular, the efficiency enhancement of optoelectronic devices, such as organic light emitting diodes (OLEDs) (Munkhbat et al, 2016;Feng et al, 2018), organic solar cells (Li et al, 2012;Vangelidis et al, 2018), and light-detectors (Xie et al, 2017), have been largely demonstrated and ascribed to the effect of their peculiar optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic NPs are widely studied for their strong scattering, absorption of light and fluorescence emission, enabling their application in several fields such as labeling, imaging, and electronics. In particular, the efficiency enhancement of optoelectronic devices, such as organic light emitting diodes (OLEDs) (Munkhbat et al, 2016;Feng et al, 2018), organic solar cells (Li et al, 2012;Vangelidis et al, 2018), and light-detectors (Xie et al, 2017), have been largely demonstrated and ascribed to the effect of their peculiar optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The rst reports using colloidal SCs as the absorbing material in a polymer matrix such as CdS and CdSe were reported more than two decades ago, 371,372 and today they commonly exceed 10% photon-toelectron conversion (PCE) efficiencies. 373 The benet of using metallic NSs in a polymer blend is their light manipulation contribution, most commonly LSPR (e.g., Au NRs, 374 Ag nanoparticles, 375 and Au/Cu 2Àx S HNSs, which exhibit a broader scattering range than standard noble metal NPs 376 ). We refer the reader for additional light management and manipulation strategies of metallic features such as incorporation into charge-selective layers, reective surfaces and additional relevant aspects of plasmonics elsewhere.…”
Section: Photovoltaicsmentioning
confidence: 99%
“…Very recently, remarkable progress in the field of OSCs using a two‐terminal monolithic solution processed tandem OSC has produced a device efficiency beyond 17%, nearly in the range of commercial silicon solar cells which have efficiencies between 18% and 22%. In the last decades, the incorporation of metal nanoparticles (MNPs) inside or near the active layer of OSCs has been revealed as an alternative strategy to enhance light trapping through the localized surface plasmon resonance (LSPR) effect, light scattering effects or a combination of both effects stemming from the MNPs . However, there are some concerns relative to the exciton quenching near the vicinity of the MNP surface or the electrical carrier traps …”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, the incorporation of metal nanoparticles (MNPs) inside or near the active layer of OSCs has been revealed as an alternative strategy to enhance light trapping through the localized surface plasmon resonance (LSPR) effect, light scattering effects or a combination of both effects stemming from the MNPs. [11][12][13][14][15][16][17] However, there are some concerns relative to the exciton quenching near the vicinity of the MNP surface or the electrical carrier traps. [18][19][20] To overcome such problems, these MNPs can be insulated with a dielectric shell as core (metal)-shell (dielectric) NPs; this successful approach was detailed in our previous studies.…”
Section: Introductionmentioning
confidence: 99%